An Investigation on the Perfomance of the Levy Collection System: a Case of Zimbabwe Tourism Authority (ZTA - Mangayi, Chido (Midlands State University, 2017)
Despite the reforms implemented to minimise non-compliance tourism, operators continue to be non-compliant in submitting levy due. Non-compliance reduces levy collected by Zimbabwe Tourism Authority (ZTA) and has thus created a gap between levy collected and the actual levy owed. The study looked at the strengths and weaknesses in the current system, reasons for non-compliance and the ways used by operators to evade levy payments and it sought to provide strategies that could be used to improve levy collection. To obtain information on the performance of the current levy system the researcher reviewed literature from other sources of work previously published by others. ZTA was examined to obtain an understanding of the views and perspectives of the reasons for the poor performance of the current levy system in collecting levy due. The research adopted a case study research design. To obtain data on the performance of the levy system questionnaires were administered to twenty-five respondents, interviews were conducted with three managers being staff and employees at ZTA and document review of secondary sources was done. From the data gathered the researcher discovered that the current system was weak and contributed immensely to the poor performance of ZTA, compliance costs in the current system discouraged compliance and under-reporting and under-invoicing were the main ways used by operators to evade payments. The researcher thus recommends that ZTA should implement an automated system of levy collection, increase the amount of risk based audits it conducts on operators, streamline the levy according to operator size as well as improve operator education and training.